Effects of VHA Policy Directive 1163 on Acceptance and Employment Rates for Veterans with Substance Use Disorders Referred to VHA Vocational Rehabilitation - Matthew E Sprong; Heaven Hollender; Ashley A Pechek; Kellie Forziat-Pytel; Frank D Buono (SAGE Publishing, 2022)
Introduction: Research has shown that Veterans with Substance/Alcohol Use Disorders (SUDs/AUDs) are at a greater risk for employment-related issues (eg, lower labor force participation rates), and interventions such as Vocational Rehabilitation (VR) have been used as a tool to reduce employment obtainment and maintenance. The purpose of the current study was to evaluate acceptance rates and employment rates at closure for Veterans with SUDs/AUDs prior to the implementation of VHA Policy Directive 1163 (mandated that Veterans are not refused services based on prior or current SUD/AUDs). SUD/AUDs were coded to reflect DSM 5-TR criteria of active use and in-remission. Methods: Data from a VHA Vocational Rehabilitation program in the Veterans Integrated Service Network 12 network were obtained for the purpose of the current study. Results: Findings showed that Veterans with AUDs were less likely to be accepted for VR services prior and after implementation of VHA Policy Directive 1163. Conclusions: When examining active and inactive SUDs/AUDs, findings showed that implementation of VHA Policy Directive 1163 was not effective for Veterans with AUDs. One factor that was not explored but could explain disparities in program acceptance rates is duration of program entry. If a Veteran has a consult placed for VHA Vocational Rehabilitation services, and their program entry date (date accepted) is a significant duration, then perhaps Veterans with active AUDs start drinking again given that they are waiting for vocational assistance. Thus, it would be important to assist Veterans with active AUDs into services in a timely manner (perhaps prior them being discharged from SUD treatment).